Coronary heart disease clinic in patients with pacemaker, and selection of optimal electrostimulation regimen - B. G. Iskenderov; V. A. Lusov; T. N. Vakina (Российский кардиологический журнал)
One hundred fifty-four patients with artificial pacemaker (АРМ) and diagnosed CHD with effort angina, functional class II-IV, were included into the trial. The influence of electrocardiostimulation (ECS) on CHD clinic was surveyed. The symptoms had improved in 72 (46, 8 %) patients (Group 1), with decreased frequency of anginal episodes, quantity and doses of antianginal drugs taken, and increased exercise capacity. The opposite was observed in another 30 (19. 5 %) patients (Group 2), with more frequent anginal episodes, changed pain type, localisation and duration, and modified reaction to nitroglycerin. It was explained by electrostimulation associated with 1. 5-2-fold increase in heart rate, raising myocardial О2 demand, as well as by psychocardial syndrome. In remained 52 patients (33. 8 %) (Group 3), the character of anginal episodes did not react to ECS. Coronary reserve optimisation requires the flexible programming of electroimpulse frequency, according to angina and/or chronic heart failure functional class, and to ECS regimen. In particular, for patients with low coronary reserve, the frequency of 55-56 impulses per min is optimal, and individuals with congestive heart failure need 75-85 impulses per min.